Synthesis and crystallographic, spectroscopic and computational characterization of 3, 3′, 4, 4′‐substituted biphenyls: effects of OR substituents on the intra‐ring torsion angle. Issue 3 (18th May 2020) - Vadra, Nahir; Suarez, Sebastian A.; Slep, Leonardo D.; Manzano, Veronica E.; Halac, Emilia B.; Baggio, Ricardo F.; Cukiernik, Fabio D.
Abstract : The synthesis, characterization and study of structures from a series of biphenyls substituted at positions 3, 3′, 4 and 4′ with groups connected to the biphenyl core through oxygen atoms are presented here. The molecular conformation is extensively studied both in the solid as well as in the liquid state, and the effect of different factors (such as packing and chain length) on the torsion angle between aromatic rings is analyzed. Abstract : Presented here are the synthesis, characterization and study (using single crystal X‐ray diffraction, Raman scattering, quantum mechanics calculations) of the structures of a series of biphenyls substituted in positions 3, 3′, 4 and 4′ with a variety of R ( R = methyl, acetyl, hexyl) groups connected to the biphenyl core through oxygen atoms. The molecular conformation, particularly the torsion angle between aromatic rings has been extensively studied both in the solid as well as in the liquid state. The results show that the compounds appearing as rigorously planar in the solid present instead a twisted conformation in the melt. The solid versus melt issue strongly suggests that the reasons for planarity are to be found in the packing restraints. A `rule of thumb' is suggested for the design of biphenyls with different molecular conformations, based on the selection of the O R substituent.